Auditoría financiera para la toma de decisiones en la Empresa Pública de Agua Potable y Alcantarillado EMAPASR-EP en la ciudad de Santa Rosa, provincia de El Oro, año 2022 - Chuquimarca Cueva, Evelyn Daniela (2023)
This research work was carried out at the " the Public Drinking Water and Sewerage Company of the canton of Santa Rosa EMAPASR-EP" in the city of Santa Rosa, province of El Oro, whose porpuse is to provide the drinking water and sewerage service that allows improving the quality of life for all santarroseños. Carrying out a financial audit in companies is of the utmost importance since without its execution there is no full assurance that decision-making is really well carried out and its results are reliable, this allows us to know the real situation of the company and your solvency. One of the objectives of the Research Project is to Measure the Level of Confidence and Risk by preparing an internal control questionnaire, which will contribute to correct decision-making for the company, at the same time, the financial audit is to verify the existence of the operations carried out through a review process to verify if any inconsistency is generated. Within the research work, everything related to the components of Cash, Banks and Inventories such as concepts and the development of the Financial Audit is detailed in the four chapters. The methods that were used in the process and elaboration of the audit are: systematic method, inductive method and deductive method; same that allowed the understanding and development of our investigated subject as an object of study that serve us to base and apply the contextualized antecedents to use and obtain results. As main discoveries of the cash component is that the cash tonnage is done empirically for which there is no documentation to support said action, the inventory component is that the warehouse manager does not have the necessary attitudes to exercise the aforementioned position in addition if there is an inadequate physical confirmation of the inventories held by the institution. In addition, the research work does not have a hypothesis because it is an audit process based on the aforementioned components, a financial audit was applied, obtaining the results, based on the specific objectives, in which finding the findings and inconsistencies to mention. Once the investigation was carried out, the following conclusions were reached that it does not have adequate control in the cash and inventory component, since the controls are carried out empirically. When comparing the collection records and the system of the Public Drinking Water and Sewerage Company of the canton of Santa Rosa EMAPASR-EP, it was found that they do not comply with an adequate analysis for decision-making, in addition, they lack a financial audit, as well as well as appropriate control tools that help to carry out an opportune analysis that reflects the real drawbacks of cash and inventories, which causes a deficiency in their registration processes and, therefore, in the financial department, which leads to making decisions wrong. Finally, it is recommended to increase a regulation or procedure that guarantees a correct analysis for the respective decision-making of the company, in addition, an adequate control of the coding of inventories to be able to keep an opportune control in the accounting records, as well as, maintain policies appropriate for the management of internal control since it will allow you to reduce the inherent risk. Keywords: financial audit, decision making, confidence level, Risk level, cash.